Daratumumab, Bortezomib, Lenalidomide, and Dexamethasone for Multiple Myeloma - Sonneveld, Pieter; Dimopoulos, Meletios A.; Boccadoro, Mario; Quach, Hang; Ho, P. Joy; Beksac, Meral; Hulin, Cyrille; Antonioli, Elisabetta; Leleu, Xavier; Mangiacavalli, Silvia; Perrot, Aurore; Cavo, Michele; et al. (The New England journal of medicine, 2024)
The addition of subcutaneous daratumumab to bortezomib, lenalidomide, and dexamethasone therapy and to lenalidomide maintenance therapy had a significant benefit on progression-free survival among patients with multiple myeloma.